The use of the condom in the first sexual relation: myth or reality? - Coutinho, Maria da Penha L; Saldanha, Ana Alayde W; Azevedo, Regina LW (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: the low age of the sexual initiation and the lack of use of condoms are the main characteristics of the increasing number of teenagers that DST/AIDS. Objective: are know the profile of the beginning of the sexual practice infected of teenager by João Pessoa, considering the use or not of the condomin this first experience, giving emphasis to the degree of affective relationship kept with the first partner. Methods: 395 teenagers of both sexes, feminine andmasculine had participated of this study, but only teenagers that had already initiated their sexual lives were, that is, 165 teenagers. Results: through the testit was verified that it has significant score differences in the average considered standards of the age of teenagers first sexual relation, considering the gender[t(159) = -3,81; p=0,000], with age average of the first sexual relation of 13,69 years old and dp=2,00 to the boys, and 15,12 years old and dp=2,33 to the girls.In the age of the partner of the first sexual relation of these teenagers, the average scores verified were t(158) = -3,52; p=0,001, but both sexes, male andfemale, had had their first experience with older people. Teenagers of female gender (79,1%) had initiated their sexual lives with the boyfriend (some of themwithout condom) and the men (54,2%), with friends or affairs (some of them also without condom). Conclusion: teenagers of João Pessoa need to bestimulated to use a preservative, therefore the number of youngsters that had not had this practice in their first sexual relation was sufficiently significant,being a preoccupying aspect in the scope of the health of these teenagers and future adults.